PENDEKATAN ILMIAH (SCIENTIFIC APPROACH) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KURIKULUM MERDEKA BELAJAR DI SDN NGADIREJO 1 KOTA BLITAR - Miftakhul Rohman; muh mirwan hariri; Fuad Ngainul yaqin; Farah Nurul Nabila; Lailatul Fauzizah (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
In this research, we will examine the scientific approach (scientific approach) in the learning of Islamic Religious Education and the Free Learning Curriculum Character in terms of the positivistic scientific paradigm initiated by Auguste Comte. Based on the results of this research, it can be explained that the scientific approach (scientific approach) in learning the Merdeka Learning curriculum is through the steps of observing, asking, reasoning, associating, and communicating. Based on the scientific approach in the Merdeka Learning curriculum, it is very relevant to the positivistic paradigm. In a positivistic perspective, in learning Islamic Religious Education and Characteristics of the Freedom to Learn curriculum, the scientific approach is less relevant to be applied to material aspects of Aqidah. Whereas in the learning material aspects of Fiqh, Morals, Al-Quran Hadith, History of Islamic Culture, the scientific approach is very good to be applied to the learning process.